Correlation between the body roundness index and chronic obstructive pulmonary disease: a cross-sectional analysis - Li, Longqian; Lin, Mingzhi; Qin, ZhuoLin; Liu, Yan; Dang, Xiangji; Wang, Cheng (Frontiers in Nutrition, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a leading cause of death worldwide, with abdominal fat, particularly visceral fat, closely associated with its onset and progression. While the lipid accumulation product (LAP) has been linked to COPD risk, it is not sufficient to fully reflect the level of visceral fat. In contrast, the body roundness index (BRI), a more accurate measure of abdominal fat distribution, has not been fully explored in relation to COPD.MethodsThe study used data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 for a cross-sectional analysis, including 24,873 participants aged over 40 years. Multivariate logistic regression models evaluated the relationship between BRI and COPD. Subsequently, sensitivity analysis, subgroup analysis, restricted cubic spline (RCS) modeling, and threshold effect evaluation were conducted.ResultsA multivariate logistic regression analysis showed that, for every 1-unit increase in the BRI, the risk of COPD increased by 5.1% (95% CI: 1.022–1.080; p < 0.001). Sensitivity analysis confirmed this conclusion (AUCBRL, 0.78745 and AUC LAP, 0.78675). In addition, the BRI is significantly better than the LAP (OR = 1.001, 95% CI: 1.000–1.001, p = 0.202) in predicting COPD. The restricted cubic spline (RCS) analysis showed a “U-shaped” relationship between the BRI and COPD, and the threshold effect analysis determined the critical point of BRI to be 3.6583.ConclusionThis study demonstrates that the body roundness index (BRI) is significantly associated with COPD risk, with a threshold effect observed at a BRI value of 3.6583. A 1-unit increase in the BRI corresponds to a 5.1% higher COPD risk. The BRI proves to be a more accurate indicator of abdominal fat distribution compared to traditional measures such as the lipid accumulation product (LAP), making it a useful tool for early COPD risk assessment and intervention.